Ab initio study of low-temperature magnetic properties of double perovskite Sr2 FeOsO6 - Kanungo, Sudipta; Yan, Binghai; Jansen, Martin; Felser, Claudia (Physical Review B - Condensed Matter and Materials Physics, 2014)
Using density-functional theory calculations, we investigated the electronic structure and magnetic exchange interactions of the ordered 3d-5d double perovskite Sr2FeOsO6, which has recently drawn attention for interesting antiferromagnetic transitions. Our study reveals the vital role played by long-range magnetic exchange interactions in this compound. The competition between the ferromagnetic nearest-neighbor Os-O-Fe interaction and antiferromagnetic next-nearest-neighbor Os-O-Fe-O-Os interaction induces strong frustration in this system, which explains the lattice distortion and magnetic phase transitions observed in experiments. © 2014 American Physical Society.
CRIS-Team Scopus Importer:2023-03-20